Cerebral white matter lesions and silent cerebral infarcts in postmenopausal women with polycystic ovary syndrome. (2nd August 2016) - Guoqing, Zhou; Fang, Sun; Lihui, Duan; Bing, Yan; Qiaoling, Peng; Yingting, Wang; Jinxia, Liu
Abstract: Objectives: The association between polycystic ovary syndrome (PCOS) and cardiovascular disease remains unclear. Our objective was to examine the relation of PCOS with cerebrovascular disease measured by brain magnetic resonance imaging (MRI) as white matter lesions (WMLs) and silent cerebral infarcts (SCIs). Methods: Seventy postmenopausal women with PCOS and 140 controls participated in the case–control, cross-sectional study. Clinical, anthropometric, hormonal and metabolic parameters were measured. WMLs and SCIs were evaluated by brain MRI. Results: Compared with controls, postmenopausal women with PCOS had higher mean body mass index, larger waist hip ratio, higher level of low-density lipoprotein cholesterol, free androgen index and lower sex hormone-binding globulin level. The PCOS group had a significantly higher prevalence of WMLs (40% versus 22%, p  =   0.009), and SCIs (17% versus 7%, p  =   0.032) compared to the control group. Conclusions: Postmenopausal women with PCOS are associated with WMLs and SCIs.